Informal or formal financing? Or both? First evidence on the co-funding of Chinese firms - Hans Degryse; Liping Lu; Steven Ongena (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
The recent financial crisis has reopened the debate on the impact of informal and formal finance on firm growth in developing countries. Using unique survey data, we find that in-formal finance is associated with higher sales growth for small firms and lower sales growth for large firms. We identify a complementary effect between informal and formal finance for the sales growth of small firms, but not for large firms. Informal finance offers informational and monitoring advantages, while formal finance offers relatively inexpensive funds. Co-funding, i.e. the simultaneous use of formal and informal finance, is the optimal choice for small firms.
URN:NBN:fi:bof-201408072082
Keywords: G21; G32; P2; 330; informal finance; formal finance; co-funding; growth